Security and provenance for Internet of Health Things: A systematic literature review. Issue 5 (15th March 2021) - Bai, Baogang; Nazir, Shah; Bai, Yuhe; Anees, Amir
Abstract: Internet of Health Things (IoHT) is an extension of the Internet of Things (IoT), which plays an important role in the observation, consultation, monitoring, and treatment process of remote exchange data processes in healthcare. The integration, computation, and interoperability are facilitated through various sensors, controllers, and actuators. Security is considered as one of the important factors for the communication of these devices to smoothly run the activities of healthcare. The current literature associated to the security of IoHT cover diverse aspects, though there is dire need of the knowledge, which can thoroughly show the review of current state‐of‐the‐art work in a systematic way. To overcome this limitation, the planned study offerings a systematic literature review (SLR) for the IoHT security and provenance. This review will support researchers to take benefit from the present literature and devise novel solutions considering the current study as evidence in IoHT. This paper focused on the security analysis and provenance for the IoHT and answering the defined questions in the current study.